2015
DOI: 10.6000/1927-7229.2015.04.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Bevacizumab During Treatment for Metastatic Colorectal Cancer

Abstract: Objective: Bevacizumab has been increasingly used in combination chemotherapy for the treatment of metastatic or recurrent colorectal cancer. The aim of this report is to underline the possible risks associated with bevacizumab use. Methods: Between July 2005 and March 2013, a total of 130 patients with metastatic colorectal cancer who received oxaliplatin as first-line chemotherapy were divided into 2 groups those treated with bevacizumab (group A) and those without (group B), and compared. The primary endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
2
1
Order By: Relevance
“…It was not statistically significant, but this case raised concern because no pulmonary effect was found when the study reinitiated chemotherapy irinotecan without bevacizumab. However, this study did not found any differences in tuberculosis cases for both bevacizumab and control groups 7 . A case–control study reported hand-foot syndrome in 58,6% cases, following co-treatment with bevacizumab and capecitabine, in which grade-3 level occurred in 5% of patients 21 .…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…It was not statistically significant, but this case raised concern because no pulmonary effect was found when the study reinitiated chemotherapy irinotecan without bevacizumab. However, this study did not found any differences in tuberculosis cases for both bevacizumab and control groups 7 . A case–control study reported hand-foot syndrome in 58,6% cases, following co-treatment with bevacizumab and capecitabine, in which grade-3 level occurred in 5% of patients 21 .…”
Section: Discussioncontrasting
confidence: 74%
“…In the hematological adverse event, the incidence of bleeding increased by adding bevacizumab to chemotherapy, but it was not statistically significant 7 , 8 , 11 , 12 , 20 , 21 . Some of the bleeding were clinically significant 7 , 8 but some were not 11 , 12 , 20 , 21 . Bleeding might be the effect of the anti-VEGF of bevacizumab, inhibiting coagulation and endothelial proliferation 7 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation